Physical and Mechanical Properties of Bamboo Oriented Strand Board Under Various Post-Thermal Treatment Duration - Silvia Uthari Nuzaverra Mayang Mangurai; Sena Maulana; Rio Ardiansyah Murda; Soleh Muhamad; Wahyu Hidayat; Yazid Bindar (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Post-treatment of bamboo-oriented strand board (BOSB) through thermal modification can be an alternative to improve BOSB quality. This study aimed to analyze the effect of post-thermal treatment duration on the physical and mechanical properties of BOSB. Three-layers BOSB with a target density of 0.7 g/cm3 was made with the core layer perpendicular to the surface and bonded with 8% phenol-formaldehyde resin. The BOSB produced was then thermally-modified at 160°C for 1, 2, and 3 h. The physical and mechanical properties of BOSB were determined based on JIS A 5908-2003 standard. The results showed that the physical properties of the thermally-modified BOSB increased while the mechanical properties decreased compared to the untreated BOSB. The moisture content (MC), water absorption (WA), and thickness swelling (TS) of BOSB decreased with the increase in post-thermal treatment duration. The decrease in MC, WA, and TS of the thermally-modified BOSB reached 38.60%, 11.92%, and 33.26%, respectively. In addition, the decrease in modulus of elasticity (MOE), modulus of rupture (MOR), and internal bonding of the thermally-modified BOSB reached 19.18%, 23.15%, and 53.51%, respectively. The results showed that TS, MOE, and MOR of the thermally-modified BOSB still could meet the 0437.0 standards for commercial OSB (Grade O-1). Keywords: bamboo-oriented strand board, Dendrocalamus asper, physical and mechanical properties, post-thermal treatment, treatment duration